2021
DOI: 10.47176/mjiri.35.53
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of volar wrist cock-up splint and dorsal lock wrist hand orthosis in reducing signs of carpal tunnel syndrome

Abstract: Several techniques have been introduced for the treatment of Carpal Tunnel Syndrome (CTS). Wrist splints reduce pain and other symptoms of CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Similarly, Weng et al [5] believe that wrist immobilization is an effective method of treatment, especially when it is also used during the day. Farahmand et al [14] suggest wearing the orthosis at night, and during the day only when the patients so wish. Halac et al [15] report that the use of the immobilizing splint at night may be an effective treatment method, but in patients with symptoms that occur only at night.…”
Section: Use Of the Orthosis During The Day/nightmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Weng et al [5] believe that wrist immobilization is an effective method of treatment, especially when it is also used during the day. Farahmand et al [14] suggest wearing the orthosis at night, and during the day only when the patients so wish. Halac et al [15] report that the use of the immobilizing splint at night may be an effective treatment method, but in patients with symptoms that occur only at night.…”
Section: Use Of the Orthosis During The Day/nightmentioning
confidence: 99%
“…According to Walker et al [16] the use of splints part-time (at night) had a more positive effect on functional activities than the use of splints full-time. The full-time use of splints is often not preferred by patients [14]. Cochrane confirmed that night immobilization is more effective than placebo, but the authors did not find a specific orthosis model that gave the best treatment results [3].…”
Section: Use Of the Orthosis During The Day/nightmentioning
confidence: 99%
See 3 more Smart Citations